Empowering Coastal Communities in Emergency Response Through Basic Life Support Training - Ida Zuhroidah; Mokh. Sujarwadi; Mukhammad Toha (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The incidence of cardiac arrest or cardiac arrest ranges from 10 out of 100,000 ordinary people aged under 35 years and annually reaches around 300,000-350,000 events. Appropriate first aid in cases of cardiac arrest is basic life support (BLS). Action that can be done is cardiopulmonary resuscitation (CPR). Cardiopulmonary resuscitation aims to restore spontaneous circulation and maintain vital organ function in cardiac arrest and stop breathing by performing chest compressions and breath support. After this training, the goal is that students will be able to play an active role and be able to provide first aid for cardiac arrest and stopping breathing appropriately, and be able to perform CPR. This activity was carried out using the method of presenting theories on the respiratory system's physiological anatomy and the circulatory system, the impact of respiratory and cardiac arrest, basic life support, and on the second day, continued with the practice of CPR through mannequins. The results obtained were most of the students (85%) understood and understood basic life support and were able to practice CPR to the mannequins even though they still needed assistance.